P3.130 Potential impact of testing for mycoplasma genitalium infection and macrolide resistance: a mathematical modelling analysis. (8th July 2017) - Chambers, Laura C; Manhart, Lisa E; Silverman, Rachel A; Barnabas, Ruanne V
Abstract : Introduction: Patients with genitourinary symptoms are generally treated syndromically with azithromycin, which can induce macrolide resistance in Mycoplasma genitalium (MG). Directing treatment based on aetiology and known macrolide susceptibility may prevent emergence of resistance. We constructed a mathematical model to evaluate the potential impact of simultaneous detection of MG and resistance markers on the percent of MG infections that are macrolide-susceptible. Methods: We developed a gender- and risk-stratified, compartmental model of MG transmission within a heterosexual population. We assumed clearance of untreated infections in 30 days; development of symptoms in 2.4% of infected men and 5.1% of infected women; initial treatment of symptomatic men and women with azithromycin; treatment of men with persistent/recurrent symptoms with moxifloxacin; 50% of infections macrolide-susceptible at baseline; de-novo macrolide resistance in 18% of susceptible bacteria after azithromycin therapy; and 100% efficacy of moxifloxacin. The model was calibrated to 1.1% population-level MG prevalence. We modelled the potential impact of using the ResistancePlus MG test (SpeeDx; Sydney, Australia) for symptomatic patients. We conducted sensitivity analyses varying the clearance rate (23–44 days) and percent of infections that are symptomatic in women (0%–11.7%). Results: The model estimated a per-partner MG transmission probability of 0.042. The model predicted that implementing the ResistancePlus test for symptomatic patients would increase the percent of MG infections that are macrolide-susceptible from 50% to 85% in 2 years. In sensitivity analyses, transmission probability estimates and 2 year percent of MG infections that are macrolide-susceptible varied from 0.032–0.047 and 82%–92%, respectively. Conclusion: Directing treatment based on aetiology and known macrolide resistance may preserve the ability to treat MG with azithromycin. Moxifloxacin therapy could be limited to patients with known macrolide-resistant MG infection and prevent treatment failure for those patients.